Estudo do potencial de associações de ZnO com os produtos naturais ácido cafeico e ferúlico como filtros solares híbridos: [recurso eletrônico] - Fernandes, Daniele Geni [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
In this work were studied associations of ZnO with the natural products caffeic and feluric acids. Two preparation methods were used, that is, the sol-gel and a reflux procedure. In the sol-gel method, ZnO is produced by the basics hydrolysis of precursors in the presence of the organic filters (caffeic and feluric acids), which results in 30 nm (or less) ZnO particles with the organic filters (in dissociated form) bonded to the surface of ZnO. In the reflux method, a dispersion of ZnO in a water/ethanol mixture was kept under reflux (50oC/4h) in the presence of the organic acids. The ZnO particles used in the reflux method have a higher diameter than sol-gel ZnO particles, but the prepared associated product ZnO/Organic acids were similar. Despite of the difference in relation to crystallinity between the products, the preparation methods resulted in analogous associations with respect to the interaction of the organic filters with the ZnO surface. The caffeic/ZnO associations presented low photostability, which lead to the degradation of the organic filter. The other associations (feluric acid/ZnO) presented satisfactory results. The FT-IR spectroscopy confirmed the formation of the association, and the nature of the bond formed compared with the Zn-O bond in Zn2+/Felutic acid complexes. The isolated organic and inorganic filters, along with the associations were analyzed by diffuse reflectance spectroscopy and Uv-vis spectroscopy. The absorption edges and the critical wavelengths were analyzed and the effects of Zn-O bonds in feluric acid/ZnO associations described as a function of the relative position of the π/π* system of the organic filter. Finally the performance of the hybrid filters were investigated in terms of the absorption of UVA and UVB radiations, with the UVA/UVB ratio, an efficiency parameter largely used in the description of solar filters, sunscreen and suncare products

Neste trabalho foram estudadas associações de ZnO com os ácidos cafeico e ferúlico, ambos produtos naturais. Foram utilizados dois métodos para a preparação das associações, isto é, o método sol-gel e o método do refluxo. No método sol-gel, ZnO resulta da hidrólise básica de precursores na presença dos filtros orgânicos (ácidos cafeico e ferúlico), formando partículas de ZnO de aproximadamente 30 nm (ou menos) de diâmetro com os ácidos na forma dissociada ligados à superfície das partículas. No método do refluxo, ZnO comercial foi mantido sob refluxo (50oC/3h) na presença dos ácidos orgânicos numa mistura água/etanol. As partículas de ZnO comercial são maiores, mas resultaram em produtos associados similares. Apesar da diferença de cristalinidade das amostras, as associações resultaram em produtos semelhantes no que diz respeito à interação filtros orgânico/inorgânico. As associações obtidas com ácido cafeico têm baixa fotoestabilidade. As demais associações apresentaram resultados satisfatórios. A associação entre os filtros foi confirmada pela espectroscopia de infravermelho e a natureza da ligação formada comparada com ligações Zn-O presentes e complexos envolvendo Zn2+ e o filtro ácido ferúlico. Os filtros separados e híbridos foram analisados por espectroscopia de reflectância difusa e espectroscopia de absorção no UV-vis. As bordas de absorção e comprimentos de onda crítico nos filtros foram analisados e o efeito de ligação das moléculas de ácido ferúlico na superfície do ZnO descrito em função da variação das posições relativas do conjunto π/π* do filtro orgânico. Finalmente, o desempenho dos filtros híbridos foi analisado em termos da absorção de radiação UUA e UVB, bem como na razão UVA/UVB, parâmetro de eficiência amplamente utilizado na formulação de filtros e protetores solares
Keywords: Óxido de zinco; Produtos naturais; Filtro solar (Cosméticos); Ácidos; Zinc oxide; Natural products; Sunscreens (Cosmetics); Acids